STRATEGI PERCEPATAN BPSDM HUKUM DAN HAM DALAM PENYELENGGARAAN PELATIHAN KEPEMIMPINAN PENGAWAS BAGI PEJABAT PENGAWAS DI LINGKUNGAN KEMENTERIAN HUKUM DAN HAM RI - M Iqbal Romzah; Firman Hadi Rivai; Bambang Giyanto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Based on The Letter of Staffing Bureau Head Number SEK.2.KP.06.02-320 dated June 23rd, 2023, supervising officers in the environment of Ministry of Law and Human Rights of Republic of Indonesia who do not follow The Supervisor Leadership Training (PKP) yet reached 1.688 people. With the limited quota every year, then that number is an urgent need and must be solved immediately. The purpose of this research was to find out why there are still many officers in the environment of Ministry of Law and Human Rights who do not follow PKP yeat and the strategy of Law and Human Rights BPSDM in carrying out the acceleration of organizing the supervisor leadership training for the supervising officers who do not follow PKP yet. The research method used was qualitative research method. The researcher chose human capital management theory proposed by Adeniji A. Anthonia and Osibanjo A. Otomayo who identified that the human capital is one of 4 (four) types of assets managed in in the organization, included the others are physical asset, the financial asset, human asset, and intangible asset. The research results showed that the financial asset in this case is the limited budget became the main factor of the high need of PKP nowadays. To identify the obstacles and arrange the acceleration strategy of PKP accomplishment in details require 4 (four) types of supporting assets started from the physical asset such as the land, building, and the supporting facility, then the human asset related to the participant and the trainers, while the financial asset is related to the budget and the intangible asset is related to the mechanism of planning and the organization culture. The suggestion which can be given is so that BPSDM of Law and Human Rights coordinate with The General Secretariat for the budget support needed and coordinate with The State Administration Institution as the guiding institution.